High Prevalence of Type 2 Diabetes in an Urban Settlement in Kerala, India - V RAMAN KUTTY, ALEYAMMA JOSEPH AND C R SOMAN (Ethnicity & Health, 1999; 4(4): 231 239, 1999)
Prevalence of type 2 or non insulin dependent diabetes mellitus is high among Indians living in India as well as abroad. Prevalence among persons of Indian origin in many countries is greater than that of people of other ethnic extraction. The Indian state of Kerala is distinguished by a high level of achievement in the health sector, characterised by both lower mortality rates and greater density of health care institutions that ensure access to most people. These attributes make the prevalence of diabetes and the pattern of its management in Kerala worth studying. Objective. To estimate the prevalence of diabetes among persons 20 years or older in an urban housing settlement in Trivandrum city, the capital of Kerala, as well as study the management of the disease in subjects affected. Design. Cross sectional survey for detecting diabetes and other chronic diseases in all willing residents of an urban housing settlement in Trivandrum, the capital city of Kerala, as part of a preventive campaign against lifestyle diseases. Fasting plasma glucose, serum triglycerides, cholesterol, height, weight and blood pressure were measured, and a detailed questionnaire administered to ascertain previous diabetic status and management.